LEARNING WRITING TEXT EXPLLANATION AND STUDY LEARNING STUDENTS VIII SMP ASSALAAM BANDUNG USING USINGTHINK METHOD OF PAIR AND SHARE - Deni Lastari; Yesi Meylani Meylani Kartiwi; Asep Kusnadi Permana (IKIP Siliwangi, 2018)
This research entitled